2012
DOI: 10.1111/dom.12042
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, multinational, randomized, placebo‐controlled, double‐blind, phase 3 trial to evaluate the efficacy and safety of gemigliptin (LC15‐0444) in patients with type 2 diabetes

Abstract: This study showed the efficacy and safety of gemigliptin 50 mg administered once daily as a monotherapy for type 2 diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 14 publications
0
49
0
Order By: Relevance
“…The overall incidence rates for adverse events were similar in the gemigliptin and placebo groups. 89 This study showed the efficacy and safety of gemigliptin 50 mg administered once daily as a monotherapy for T2DM patients.…”
Section: Monotherapymentioning
confidence: 72%
See 1 more Smart Citation
“…The overall incidence rates for adverse events were similar in the gemigliptin and placebo groups. 89 This study showed the efficacy and safety of gemigliptin 50 mg administered once daily as a monotherapy for T2DM patients.…”
Section: Monotherapymentioning
confidence: 72%
“…Next, a 24-week, randomized, double-blind, placebo-controlled Phase III trial was conducted in 182 patients (74 from Korea and 108 from India) with T2DM. 89 After an initial 2 weeks of a diet and exercise program followed by 2 weeks of a single-blind placebo run-in period, eligible patients were randomized to gemigliptin 50 mg or placebo, receiving the assigned treatment for 24 weeks. HbA 1C and FPG were measured periodically, and oral glucose tolerance test was performed at baseline and weeks 12 and 24.…”
Section: Monotherapymentioning
confidence: 99%
“…24 In addition, a recently performed phase III study conducted in 182 patients with type 2 diabetes mellitus including Korean and Indian populations also showed that 24 weeks of LC15-0444 treatment at a dose of 50 mg per day led to significant reductions in HbA1c and FPG levels. 25 In a metformin add-on trial performed in 425 Asian patients with inadequately controlled type 2 diabetes being treated with metformin alone, gemigliptin showed comparable efficacy and safety profiles to sitagliptin. 26 In the present study, we observed that the increased urinary excretion of 8-isoprostane after UUO, reflecting the increased oxidative stress in the kidney, was attenuated in mice treated with LC15-0444.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, gemigliptin inhibits DPP IV activity, which results in increases in GLP-1 and GIP levels and subsequent insulin responses, eventually improving glycemic control. In clinical studies conducted in Korean subjects with type 2 diabetes, gemigliptin monotherapy (50 mg for 12 weeks) effectively improved glycosylated hemoglobin (HbA1c) level, fasting plasma glucose level, oral glucose tolerance test results, b-cell function and insulin sensitivity measures (Noh et al, 2012;Rhee et al, 2010;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%